The impact of the Chief Executive Officer Power on the level of accounting disclosure of performance and its reflection on the company’s value in light of agency theory - an applied study on Jordanian industrial companies - محمد علي الفضل مؤيد (Dirasat in Economics and Business, 2024)
This study aims to provide evidence derived from the reality of the Jordanian environment application about the impact of the CEO’s influence on the level of disclosure of sustainability activities and its reflection on the company’s value in light of the contents of agency theory. This is to refute or confirm the idea that the importance of disclosing sustainability performance in influencing the market value of the company linked to the influence of managers, which determines the level of quantity and quality of information disclosed in financial reports. This study has been conducted according to a sample of 38 industrial companies for the period 2017–2021. It constitutes 52.8% of the total number of companies in the Jordanian industrial sector. The study has been found that 77.6% of the change in the level of disclosure of sustainability performance has been explained by variables related to the influence of the CEO that are related to the percentage of administrative ownership. Also, the duration of the director’s stay in his position and the separation between the positions of CEO and Chairman of the Board of Directors. Concerning the variable of the board directors’ independence, the results do not show any effect on the level of sustainability disclosure in explaining the change in the company’s market value. The results are also shown that the level of disclosure about sustainability performance is powerful in explaining the change in the company's market value when the CEO influence variables are entered into the test model. It has clearly increased more than it was before the test model included these variables, which supports the researcher’s opinion regarding the impact of the elements of the CEO’s influence on the level of disclosure of sustainability performance and then the market value of the company.